2012
DOI: 10.1063/1.4737188
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of nanosecond pulsed laser ablation and the application to momentum coupling

Abstract: Articles you may be interested inOptical time of flight studies of lithium plasma in double pulse laser ablation: Evidence of inverse Bremsstrahlung absorption Phys. Plasmas 21, 063110 (2014); 10.1063/1.4885107Experimental and computational study of complex shockwave dynamics in laser ablation plumes in argon atmosphere Phys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Sinko and Phipps also found a similar relationship between C m and laser wavelength [23]. Besides, it was reported that the C m increased with the decrease in laser wavelength under the same laser intensity and pulse width [24], indicating the shorter laser wavelength was more advantageous for the momentum coupling of laser to the target. In contrast with the Phipps theory, Zheng et al reported that the C m of 1064 nm was higher than that of 532 nm for bulk liquid ablation [13].…”
Section: Introductionmentioning
confidence: 63%
“…Sinko and Phipps also found a similar relationship between C m and laser wavelength [23]. Besides, it was reported that the C m increased with the decrease in laser wavelength under the same laser intensity and pulse width [24], indicating the shorter laser wavelength was more advantageous for the momentum coupling of laser to the target. In contrast with the Phipps theory, Zheng et al reported that the C m of 1064 nm was higher than that of 532 nm for bulk liquid ablation [13].…”
Section: Introductionmentioning
confidence: 63%
“…As a consequence, in this work we focused on LA, in vacuum, of an aluminum target generated by a Gaussian-shaped laser pulse of 20 duration (FWHM) with a peak intensity of the order of . The choice of this target material naturally arises by considering that a consistent part of space debris is made of aluminum [ 8 ] and that aluminum is also widely used in LAP, both as a propulsion performance standard [ 9 ] and as a case study for propulsion optimization [ 10 ].…”
Section: Introductionmentioning
confidence: 99%